Productivity losses in smoking breaks on construction sites: a case study - Yung, Ping; Agyekum-Mensah, G. (Emerald, 2012)
Purpose: This paper aims to examine the extent of productivity losses in smoking breaks on construction sites. Design/methodology/approach:The smoking behaviours of workers in a small/medium-sized construction company were examined for a period of four months. Construction workers were targeted due to their higher prevalence in smoking. The exact time losses through smoking breaks were measured and calculated. The productivity losses were then evaluated and compared with the estimates of productivity losses and wage penalties found in the literature. Findings: It is found that a smoker on average smokes 5.6 cigarettes, which takes a total of 73 minutes, representing 15.2 per cent of productivity loss in an eight-hour shift. This productivity loss is much higher than productivity losses through increased sick leaves or the wage penalties for smokers found in the literature. Research limitations/implications: Variations of smoking behaviours throughout the year have not been considered. The study has focused on a renovation and rehabilitation project, it has not considered the workers from other trades who might have different smoking behaviours. Originality/value: This paper is a contribution to the limited literature on the productive time losses through smoking breaks. Most studies on productive time loss attributable to smoking focused on the additional sick leaves taken by the smokers, without realizing that productive time losses through smoking breaks far exceeds those additional sick leaves.